Loss of Trabid, a new negative regulator of the drosophila immune-deficiency pathway at the level of TAK1, reduces life span. - Merennege Dilan Anush Fernando; Ilias Kounatidis; Petros Ligoxygakis (PLoS Genetics)
A relatively unexplored nexus in Drosophila Immune deficiency (IMD) pathway is TGF-beta Activating Kinase 1 (TAK1), which triggers both immunity and apoptosis. In a cell culture screen, we identified that Lysine at position 142 was a K63-linked Ubiquitin acceptor site for TAK1, required for signalling. Moreover, Lysine at position 156 functioned as a K48-linked Ubiquitin acceptor site, also necessary for TAK1 activity. The deubiquitinase Trabid interacted with TAK1, reducing immune signalling output and K63-linked ubiquitination. The three tandem Npl4 Zinc Fingers and the catalytic Cysteine at position 518 were required for Trabid activity. Flies deficient for Trabid had a reduced life span due to chronic activation of IMD both systemically as well as in their gut where homeostasis was disrupted. The TAK1-associated Binding Protein 2 (TAB2) was linked with the TAK1-Trabid interaction through its Zinc finger domain that pacified the TAK1 signal. These results indicate an elaborate and multi-tiered mechanism for regulating TAK1 activity and modulating its immune signal.